An unpublished Latin poem by Juan Arce de Otálora (Minerva, 2020)
This is an edition, translation and commentary on an unpublished poem by Juan Arce de Otalora, addressed to the constable Pedro Fernández de Velasco y Tovar.
Keywords: Juan Arce de Otálora; textual criticism; reception of classical literature.; Humanistic Latin poetry